BIOM-24. PROTEIN SURFACE SIGNATURE ON SERUM EXTRACELLULAR VESICLES FOR NON-INVASIVE DETECTION OF TUMOR PROGRESSION IN GLIOBLASTOMA PATIENTS. (12th November 2021) - Tzaridis, Theophilos; Weller, Johannes; Bachurski, Daniel; Shakheri, Farhad; Schaub, Christina; Hau, Peter; Buness, Andreas; Schlegel, Uwe; Steinbach, Joachim; Seidel, Clemens; Goldbrunner, Roland; Schäfer, Niklas; et al.
Abstract: INTRODUCTION: Detection of tumor progression in glioblastoma patients remains a major challenge for clinicians due to equivocal MRI results. Extracellular vesicles (EVs) are potential biomarkers and can be detected in the blood of tumor patients. In this study, we evaluated the potential of serum-derived EVs from glioblastoma patients to serve as a marker for tumor progression in adjunction with MRI assessment. METHODS: Glioblastoma patients from two independent cohorts, one from the multicenter Phase III CeTeG/NOA-09 trial (n=36) and the other from patients treated at the University of Bonn (n=31), were included in this study. EVs from serum of glioblastoma patients and healthy volunteers were separated by size exclusion chromatography and ultracentrifugation. EV markers were defined by using a proximity-extension assay and bead-based flow cytometry. Tumor progression was defined according to modified RANO criteria. RESULTS: EVs from the serum of glioblastoma patients (n=67) showed an upregulation of CD29 (p=0.08), CD44 (p< 0.0001), CD81 (p< 0.0001), CD146 (p< 0.0001), C1QA (p=0.003), and histone H3 (p< 0.0001) as compared to serum EVs from healthy volunteers. For both independent cohorts of glioblastoma patients, we noted upregulation of C1QA, CD44, and histone H3 upon tumor progression, but not in patients with stable disease. Notably, six patients with worse survival compared to the median survival of the cohort did not fulfill RANO criteria at the time of suspected progression, yet showed an elevation of at least one out of these three markers. In a multivariable logistic regression analysis, a combination of CD29, CD44, CD81, C1QA, and histone H3 correlated with RANO-defined tumor progression with an AUC of 0.76. CONCLUSION: Measurement of CD29, CD44, CD81, C1QA, and histone H3 in serum-derived EVs of glioblastoma patients, along with standard MRI assessment, could improve detection of true tumor progression and thus be a useful tool for clinical decision making.